Idea of thaqâfah and culture in the Muslim and Western conception - Mohammed Hussein Boayo, Suleiman (IDOSI, 2011)
The essence and conception of the term thaqafah have been a problematic issue in Islamic civilization since Ibn Khaldun’s works. The chief reason is that this term has a linguistic and historical complexity as yet unsolved by writers and scholars. Consequently, this had led to confusion in the usage and concept of thaqâfah, which is an Arabic term that conveys the concept of ‘culture’ in the Western sense. The linguistic and historical aspects of the terms thaqâfah and ‘culture’ will be discussed in this paper. Their linguistic origins, primary and secondary usage, as well as the development of their meanings overtime will be clarified, especially with regard to the concept of culture, which will make the general theme of this paper more comprehensible. These terms have importance in modern society and civilization. The changes in their usage and meaning at this time indicate a general change in our ways of thinking and living, as well as in the ways we manage our social, political and economic institutions. The term ‘culture’ in the Western sense is already known by its complete development and acquisition of new and important meanings. This is so partly because of its intricate historical development. Our main aim in this paper is therefore to focus on the problem of the concept of the term thaqâfah, how it was used in Islamic history, when it acquired its recent concept and the Western connotation as a social phenomenon and the reaction of the Muslim scholars to that acquisition.